The correlation between the National College Entrance Examination scores and the academic grades of the 1974-1976 graduates of San Agustin Academy, Panglao, Bohol - Clemen, Filomena P. (Animo Repository, 1977)
v. 1. This was a descriptive study, the purpose of which was to investigate the extent of relationship between the NCEE scores of fourth year students and their academic grades in three subject areas, namely, English, applied arithmetic and physics as well as their academic general averages. The subjects were one hundred and sixty-seven high school graduates from San Agustin Academy, Panglao, Bohol during the school years 1973-1974, 1974-1975 and 1975-1976. Eight variables were used in this study. The NCEE scores could be categorized as the NCEE variables and the academic grades in the fourth year, as academic variables. The Pearson Product-Moment Coefficient of Correlation was used to determine the relationship between the variables. The value of r from each computation was then referred to the table of values of r for different levels of significance. This study sought to answer the following questions: 1) What is the correlation between the students' NCEE scores in English and their academic grades in English? 2) How far do the NCEE scores in Mathematics correlate with the student's achievement in Applied Arithmetic? 3) To what extent are the NCEE scores in Science related to the student's academic grades in Physics? 4) Is there a correlation between the NCEE General Scholastic Aptitude and the students' general average in the fourth year? v. 2. For the past few years, San Agustin Academy has increased in student population consequently, more teachers have been employed. The school is fully aware of its goal as an educational institution, but it does not have any written guidelines for the faculty to make them work together harmoniously with the administration and fulfill their roles as expected for the attainment of its defined goals. The absence of written and definite guidelines about the basic principles and practices of conducting a school with an increasing population and the desire to improve the administrative system, gave rise to the making of this project. Direct observations and established practices in school and the community some practices found in other faculty handbooks policies found in the manual of regulations for private schools and New Labor Code of the Philippines, were the sources gathered and consulted for the formulation of the proposed handbook. This faculty handbook, allocate the functions, duties and responsibilities of the specified personnel for the success of their expected roles. This is aimed to serve as a source of school policy and procedures, which concern mostly the faculty. v. 3. St. Philomel Institute is a Catholic institution of learning. In the first few years of its existence, SPI was financially unstable. It was only a few years ago when its enrollment rapidly increased, owing to the already education conscious parents. Father Pedro Redondo, the democratic and humanistic Director of St Philomel Institute and a devoted parish priest was grabbed by two alternatives which were equally conclusive against him as a leader and educational manager, whether he would dismiss Mr. Roberto Reda or not. He was in the state of difficulty to determine what course to pursue. Roberto Reda, the target of the fiery hatred of the school supporters, was one of the only two male teachers in the school, which was in dire need of at least two male members of the faculty. His parents were influential persons in the community and assets to the parish. On the contrary, he had committed three serious transgressions during his course of teaching in the institution. On the other hand, the parents who were eagerly after his dismissal before another school year would begin, were, in one way or another, the backbone of the financial framework of the then flourishing school. In this particular case study, alternatives were provided to help Father Redondo deal with this dilemma.